PATHFINDING PROBLEM BASED ON GREEDY ALGORITHMS: ANALYSIS USING DIJKSTRA'S ALGORITHM AS AN EXAMPLE - Hamroyeva Ozoda (Bright Mind Publishing, 2025)
This article analyzes the problem of pathfinding based on greedy algorithms. The main focus is on Dijkstra's algorithm, and its operating principle, advantages, and limitations are considered. The problem of pathfinding is relevant in modern technologies, in particular in the fields of navigation systems, transport logistics, games, and artificial intelligence. Dijkstra's algorithm tries to find the overall optimal path by selecting a local optimal solution at each stage. This article analyzes the theoretical foundations of the algorithm, as well as practical examples. It also justifies the greedy approach of Dijkstra's algorithm and briefly compares it with other pathfinding algorithms.
Keywords: Greedy algorithms, Dijkstra's algorithm, pathfinding problem, graph theory, optimal solution, algorithmic approach, navigation systems, transport logistics, artificial intelligence, computer graphics.